Women’s Role in Violence and UN Women, Peace, and Security Agenda - Çağlayan Başer (Alternatif Politika)
The UN’s Women, Peace, and Security (WPS) agenda emphasizes women’s victimhood and peacemaking roles. However, women participate in two-thirds of armed movements and affect conflict outcomes in unique gendered ways. This article argues that excluding female perpetrators from the WPS agenda generates new insecurities for them and broader societies. By highlighting women’s contribution to perpetuating conflict, I propose a framework to incite policymakers to view women’s empowerment as a mainstream security concern and implement policies aligned with the goals of the UN WPS Agenda. First, I explore reasons to avoid reinforcing gender norms that portray women as victims and peacemakers. These reasons encompass assessing: 1) women’s contributions to armed organizations, 2) their exclusion from post-conflict rehabilitation programs, 3) the limited visibility of human rights violations by women and the underrepresentation of male civilians as victims, and 4) “saving vulnerable women” rhetoric as a justification for Western power involvement. Then, I examine gender inequality as a fundamental cause enabling these factors, underscoring the need to regard gender inequality and traditional gender norms as central security concerns.